Can hotel employees arise internal whistleblowing intentions? Leader ethics, workplace virtues and moral courage - Ibrahim M. Mkheimer; Kareem M. Selem; Ali Elsayed Shehata; Kashif Hussain; Marta Perez Perez (European Journal of Management and Business Economics, 2023)
Purpose – This study investigates the relationship between leaders' ethical behaviors and internal whistleblowing among hotel employees through the mediation role of organizational virtuousness. According to the conceptual framework, ethical leadership creates a virtuous workplace and encourages whistleblowing. Design/methodology/approach – A survey approach with responses of 442 employees from Egyptian five-star hotels was used. Structural equation modeling (SEM) was used to test the hypotheses proposed based on leader–member exchange (LMX) and ethical leadership theories. Findings – Ethical leadership has a favorable impact on organizational virtuousness and, as a result, has a significant impact on whistleblowing intention. The ethical leaders–subordinates' intents to whistleblow association partially mediated organizational virtuousness. To assist them in reporting ethics violations, most hotel employees require organizational characteristics, such as organizational climate and psychological empowerment, in addition to individual characteristics, such as moral bravery and ethical efficacy. Originality/value – The conceptual framework of this paper adds a new guide for future research related to the hospitality literature, which is how employees' intent to internal whistleblowing. As such, senior management should serve as a moral role model for hotel employees, inspiring them to be moral and allowing them to participate in decision-making. 研究目的 – 本研究擬透過組織德行所扮演的仲介角色，去探討領導者的道德行為與酒店員工間內部舉報的相互關係。根據有關的概念框架，領導倫理會為機構創造一個富有道德的工作場所，以及鼓勵員工互相舉報不當的行為。 研究設計/方法/理念 – 研究採用調查方法進行，數據來自442名於埃及五星級酒店工作的僱員的回覆。研究人員以結構方程模型來測試研究的假設 － 研究的假設乃根據領導者－成員交換理論和倫理型領導理論而提出的。 研究結果 – 領導倫理會給組織美德帶來積極的影響，因此，領導倫理也會給舉報動機帶來重要的影響。領袖－下屬舉報合夥人合乎道德的動機，對組織美德起著仲介作用。若要酒店僱員舉報違反道德規範的行為，除了僱員須有個人特質、如道德勇氣和倫理效能等之外，酒店亦須具備一些組織特徵、如組織氛圍和心理賦權等。 研究的原創性/價值 – 本研究的概念框架，給探討僱員作內部舉報行為的動機的學者提供新的指引，為餐旅業的研究提供方向。組織的高級管理人員應以身作則，為僱員建立道德典範，鼓勵他們遵循道德規範而行事，並容許他們參與決策。